Cultural conceptions : on reproductive technologies and the remaking of life - Hartouni, Valerie (University of Minnesota Press, 1997)
What happens to prevailing beliefs about the uniqueness of individual life when life can be cloned? Or to traditional understandings of family relationships when a child can have up to five parents? These are some of the questions addressed by Valerie Hartouni in her consideration of the cultural effects of new reproductive technologies as reflected in video images, popular journalism, scientific debates, legal briefs, and policy decisions. In Cultural Conceptions, Hartouni tracks the circulation and communication of various myths, images, and stories pertaining to new reproductive technologies.